1999
DOI: 10.1136/ard.58.5.309
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoptotic peripheral blood neutrophils in systemic lupus erythematosus: relations with disease activity, antibodies to double stranded DNA, and neutropenia

Abstract: Objective-To quantify the percentage of apoptotic peripheral blood neutrophils in systemic lupus erythematosus (SLE) and to determine the relations with disease activity and neutropenia. Methods-Neutrophil apoptosis in SLE patients (n =50) was assessed by flow cytometry using annexin V binding and fluorescent labelled anti-fas. Rheumatoid arthritis (RA, n =20) and inflammatory bowel disease patients (IBD, n =20) were studied as disease controls. Results-The percentage of apoptotic neutrophils, determined by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
4
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(163 citation statements)
references
References 43 publications
12
144
4
3
Order By: Relevance
“…2 SLE patients have displayed increased apoptosis of lymphocytes, particularly T cells, neutrophils, and monocytes. [3][4][5][6][7][8] Defective apoptosis is thus a vital part of SLE pathogenesis. Furthermore, altered monocyte phenotypes and neutropenia lead to impaired recognition and clearance of apoptotic cells, and correlate with anti-dsDNA and disease activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 SLE patients have displayed increased apoptosis of lymphocytes, particularly T cells, neutrophils, and monocytes. [3][4][5][6][7][8] Defective apoptosis is thus a vital part of SLE pathogenesis. Furthermore, altered monocyte phenotypes and neutropenia lead to impaired recognition and clearance of apoptotic cells, and correlate with anti-dsDNA and disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, altered monocyte phenotypes and neutropenia lead to impaired recognition and clearance of apoptotic cells, and correlate with anti-dsDNA and disease activity. 6,[9][10][11] Fas ligand (FasL), a trimeric type II membrane protein, belongs to the TNF receptor family that induces apoptosis of cells bearing Fas receptor. 12 Observations in mouse models of SLE demonstrated that mice with Fas (MRL/lpr) or FasL (gld) mutations developed lymphadenopathy with accumulation of CD4ÀCD8À double negative lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Supported also by results from lupus animal models, apoptosis of lymphocytes, monocytes as well as neutrophils have been reported to be accelerated in SLE [113][114][115]. In addition, several groups have reported defective processing, and FcR-dependent clearance, of ICs and apoptotic cells in lupus patients [116][117][118].…”
Section: Sle and The Waste Disposal Hypothesismentioning
confidence: 95%
“…SLE patients have a dysregulation in apoptosis with decreased clearance of apoptotic bodies that are released in the serum. 37,38 These circulating apoptotic bodies, double-stranded DNA fragments and nucleosomes likely serve as autoantigen for autoreactive B cells. 39 Exposure to these antigens, subsequently causes the generation of anti-nuclear antibodies such as anti-DNA.…”
Section: Pathogenesis Of Lupus Nephrtitismentioning
confidence: 99%